Pre-Clinical Study of the [18F]AlF-Labeled HER2 Affibody for Non-Invasive HER2 Detection in Gastric Cancer - Han, Jingya; Chen, Yang; Zhao, Yan; Zhao, Xinming; Zhang, Jingmian; Wang, Jianfang; Zhang, Zhaoqi (Frontiers in Medicine, 2022)
Human epidermal growth factor receptor 2 (HER2) is an important biomarker in gastric cancer (GC) and directly influences the therapeutic effect. Fluorine is firmly bound to Al3+ forming [18F]AlF-1,4,7-triazacyclononanetriacetic acid (NOTA)-HER2 affibody is a promising radiolabeled tracer that can monitor the changes of HER2 expression combining the advantages of simple preparation and the properties of 18F. The aim of this study was to develop a quick method for the synthesis of [18F]AlF-NOTA-HER2 affibody and evaluate its utility for HER2+ GC imaging in mouse models. Moreover, 68Ga-NOTA-HER2 affibody imaging was also performed to highlight the superiority of [18F]AlF-NOTA-HER2 affibody imaging in resolution. The HER2 affibody was conjugated with NOTA and labeled using 18F based on the complexation of [18F]AlF by NOTA. Its quality control and stability were performed by high-pressure liquid chromatography (HPLC). The molecular specificity and binding affinity of the novel radiotracer were evaluated in the GC cell line with HER2 overexpression (NCI-N87) and negative expression (MKN74). Distribution studies and PET/CT imaging were performed in mouse models. 68Ga-NOTA-HER2 affibody PET/CT imaging was also performed. [18F]AlF-NOTA-HER2 affibody was efficiently prepared within 30 min with a non-decay-corrected maximum yield of 32.69% and a radiochemical purity of more than 98%. [18F]AlF-NOTA-HER2 affibody was highly stable in incubation medium for 4 h in vitro and in the blood of nude mice at 30 min post-injection (p.i.). In vitro studies revealed specific binding and high binding affinity of the probe in NCI-N87 cells, while no binding was seen in MKN74 cells. PET imaging showed that NCI-N87 xenografts were differentiated from MKN74 xenografts with excellent contrast and low abdominal background, which was confirmed by the distribution results. High-level accumulation of the [18F]AlF-NOTA-HER2 affibody in HER2+ tumors was blocked by excess unlabeled NOTA-HER2 affibody. [18F]AlF-NOTA-HER2 affibody has a higher image resolution than that of 68Ga-NOTA-HER2 affibody. [18F]AlF-NOTA-HER2 affibody could be produced facilely with high radiochemical yield and may serve as a novel molecular probe with tremendous clinical potential for the non-invasive whole-body detection of the HER2 status in GC with good image contrast and resolution. This method could provide an in vivo understanding of GC biology that will ultimately guide the accurate diagnosis and treatment of GC.